The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation - Fares, S; Mereu, S; Scarascia Mugnozza, G; Vitale, M; Manes, F; Frattoni, M; Ciccioli, P; Gerosa, G; Loreto, F (Biogeosciences, 2009)
Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a ﬁeld campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contribution of the largely biodiverse dune vegetation, a prominent component of the Mediterranean ecosystem, was overlooked. While speciﬁc aspects of the campaign will be discussed in companion papers, the general climatic and physiological aspects are presented here, together with information regarding BVOC emission from the most common plant species of the dune ecosystem. During the campaign regular air movements were observed, dominated by moderate nocturnal land breeze and diurnal sea breeze. A regular daily increase of ozone concentration in the air was also observed, but daily peaks of ozone were lower than those measured in summer on the same site. The site was ideal as a natural photochemical reactor to observe reaction, transport and deposition processes occurring in the Mediterranean basin, since the sea-land breeze circulation allowed a strong mixing between biogenic and anthropogenic emissions and secondary pollutants. Measurements were run in May, when plant physiological conditions were optimal, in absence of severe drought and heat stress. Foliar rates of photosynthesis and transpiration were as high as generally recorded in unstressed Mediterranean sclerophyllous plants. Most of the plant species emitted high level of monoterpenes, despite measurements being made in a period in which emissions of volatile isoprenoids could be restrained by developmental and environmental factors, such as leaf age and relatively low air temperature. Emission of isoprene was generally low. Accounting for the high monoterpene spring emission of the dune ecosystem may be important to correct algorithms at regional and ecosystem levels, and to interpret measurements of ﬂuxes of volatile isoprenoids and secondary pollutants.
Keywords: BVOC emission; Castelporziano; Mediterranean ecosystem; stress (voyant); Water availability

Coupling water sources and carbon metabolism of natural vegetation at integrated time and space scales - Valentini, R; Scarascia Mugnozza, G; De Angelis, P; Matteucci, G (Agricultural and Forest Meteorology, 1995)
The linkage between water utilization and photosynthetic processes is investigated using stable isotopes and eddy covariance techniques, allowing integration of physiological pro- cesses both at time and space scales, respectively. Using the ratio of the stable isotopes of hydrogen (hydrogen vs. deuterium) and discrimination of 13C vs. ~2C, the relationship between water sources (rain water vs. ground water) utilization and intercellular carbon dioxide con- centration is analysed for various species of two different ecosystems: an alpine forest and a Mediterranean macchia. As an example of space scale integration of water-carbon coupling, the relationship between canopy carbon dioxide assimilation and bulk stomatal conductance, measured with eddy covariance, is presented for a macchia community and a low-productivity grassland.
Keywords: canopy conductance; canopy photosynthesis (voyant); carbon isotope discrimination; water use